Inequality and Redistribution via the Public Provision of Private Goods - Margarita Katsimi; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2004)
The relationship between inequality and redistribution is usually studied under the assumption that the government collects different amounts of taxes from each citizen (voter) but gives back the same amount (in cash or in kind) to everyone. In this paper we consider what happens if the government can redistribute through both sides of its budget (revenue and expenditure). We show that inequality may have no discernible effect on the size of redistributive programs.
Keywords: 330; redistribution; inequality; public goods; median voter